Electrolyte with high voltage stability and secondary battery
By using mixed solvents of PC, FEC and FEMC in the sodium ion battery electrolyte, combining mixed conductive salts of sodium perchlorate and sodium hexafluorophosphate, as well as sodium nitrate and sodium acesulfame as additives, the composition of the electrolyte is optimized, solving the shortcomings of the existing electrolyte in terms of oxidative stability and cycling performance, and achieving high energy density and long cycle life of sodium ion battery.
Patent Information
- Application Number
- CN202411913650.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing sodium ion battery electrolyte has shortcomings in oxidation stability and cycling performance, which affects the high energy density and long cycle life of the battery.
The composition of the electrolyte is optimized by combining mixed solvents of PC, FEC and FEMC, combining mixed conductive salts of sodium perchlorate and sodium hexafluorophosphate, as well as sodium nitrate and sodium acesulfame as additives.
It significantly improves the ionic conductivity, oxidation stability and cycling performance of the electrolyte, ensures the high energy density and long cycle life of the sodium ion battery, and improves the rate performance and safety of the battery.
Smart Images

Figure BDA0005206339810000091 
Figure BDA0005206339810000101 
Figure BDA0005206339810000111
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy, in particular to an electrolyte for a secondary battery and a secondary battery. Background Art
[0002] Sodium-ion battery is a secondary battery (rechargeable battery) that mainly relies on the movement of sodium ions between the positive and negative electrodes to work, similar to the working principle of lithium-ion batteries. The charging and discharging process of sodium-ion batteries relies on the movement of sodium ions between the positive and negative electrodes. When charging, sodium ions are released from the positive electrode and embedded in the negative electrode through the electrolyte; when discharging, the opposite is true, sodium ions are released from the negative electrode and return to the positive electrode, while electrons move through the external circuit to form an electric current.
[0003] Sodium-ion batteries are mainly composed of positive electrodes, negative electrodes, separators, current collectors, electrolytes, etc. Among them, positive electrode materials can generally be divided into layered transition metal oxides, polyanionic compounds, and Prussian blue compounds. Negative electrode materials are mainly divided into carbon materials and non-carbon materials. The function of the separator is to physically separate the positive and negative electrodes to avoid direct contact and reaction between the two, while also ensuring the infiltration and penetration of solvent molecules to allow the rapid passage of solvated sodium ions. Commonly used separators include PP film, PE film, PP / PE composite film, etc. The current collector is generally aluminum foil, because sodium does not react with aluminum at low potential, and the cost of aluminum is lower than that of copper. The electrolyte is composed of solvents, sodium salts, and additives, which have an important impact on the energy density, cycle life, and rate performance of the battery.
[0004] Sodium-ion batteries have many advantages. First, sodium is abundant in the earth's crust and its resource richness is significantly higher than that of lithium, which makes the raw material cost of sodium-ion batteries relatively low. Secondly, sodium-ion batteries have good fast charging performance and are expected to shorten the charging time. In addition, sodium-ion batteries have a wide operating temperature range and can maintain a good capacity retention rate in both low and high temperature environments. They also have good safety performance and will not catch fire or explode in tests such as overcharging, over-discharging, short circuiting, puncture, and extrusion. Finally, the production process of sodium-ion batteries is similar to that of lithium-ion batteries, the equipment is highly compatible, and the cost of enterprise production line conversion is low.
[0005] The electrolyte solvents of sodium ion batteries mainly include ester solvents and ether solvents. Ester solvents mainly include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), etc. Ether solvents mainly include ethylene glycol dimethyl ether (DME) and dioxolane (DOL), etc. Ester solvents have good solubility for sodium salts, can provide good ion transmission ability when used as electrolytes, and have a relatively stable structure, oxidation resistance, and high safety. Although ether solvents can promote the insertion of sodium ions between carbon material layers, improve the specific capacity, first coulomb efficiency and rate performance of the material, they are easy to generate peroxides, have poor oxidation resistance, are prone to ignition during application, and have poor safety.
[0006] The additives for sodium-ion battery electrolyte are mainly divided into film-forming additives, flame retardant additives, overcharge protection additives, etc.
[0007] The invention provides a new sodium ion battery electrolyte and a secondary battery. Summary of the invention
[0008] The present invention provides an electrolyte for a sodium ion battery, comprising:
[0009] A solvent, wherein the solvent is a mixture of propylene carbonate (PC), fluoroethylene carbonate (FEC) and methyl trifluoroethyl carbonate (FEMC);
[0010] Conductive salt, wherein the conductive salt is a mixture of sodium perchlorate (NaClO4) and sodium hexafluorophosphate (NaPF6);
[0011] Additives, the additives comprising sodium nitrate (NaNO3) and acesulfame sodium.
[0012] Furthermore, the volume ratio of the components in the solvent is PC:FEC:FEMC is 4-5:2-3:2-3.
[0013] Furthermore, the molar ratio of the sodium perchlorate to sodium hexafluorophosphate is 1:0.1 to 1:0.5, and the mass percentage of the conductive salt in the electrolyte is 10% to 25%.
[0014] Furthermore, the mass percentage of the conductive salt in the electrolyte is 18%.
[0015] Furthermore, the addition amount of the sodium nitrate and sodium acesulfame is 0.1%-2% of the total mass of the electrolyte respectively.
[0016] Further, the following steps are adopted:
[0017] Dry PC, FEC and FEMC to ensure that the moisture content is less than 10ppm;
[0018] In a protective gas atmosphere, the three solvents are mixed evenly according to a predetermined ratio;
[0019] Add conductive sodium salt and additives and continue stirring until completely dissolved;
[0020] Filter the prepared electrolyte through a filter membrane to remove possible solid particles and impurities.
[0021] A sodium ion secondary battery using the above electrolyte.
[0022] It is characterized in that the positive electrode active material of the sodium ion secondary battery is sodium vanadium phosphate (Na3V2(PO4)3, NVP), and the amount of the positive electrode active material accounts for 70%-80% of the total mass of the positive electrode.
[0023] Characterized in that the negative electrode material of the sodium ion secondary battery is hard carbon.
[0024] Characterized in that the manufacturing steps of the sodium ion secondary battery include:
[0025] The positive electrode active material, the conductive agent and the binder are mixed evenly and coated on the aluminum foil to form a positive electrode sheet;
[0026] The negative electrode material, the conductive agent and the binder are mixed evenly and coated on the copper foil to form a negative electrode sheet;
[0027] Winding the positive electrode sheet, the negative electrode sheet and the separator to form a battery core;
[0028] The battery cell is placed in a battery case, the electrolyte is injected, and the battery case is sealed.
[0029] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0030] The present invention optimizes the electrolyte solvent composition and adopts a mixture of PC, FEC and FEMC, thereby significantly improving the ionic conductivity, oxidation stability and cycle performance of the electrolyte, providing a high-performance electrolyte for the sodium ion secondary battery and ensuring the high energy density and long cycle life of the battery.
[0031] The use of a mixed conductive salt of sodium perchlorate and sodium hexafluorophosphate, as well as sodium nitrate and sodium acesulfame as additives further improved the composition of the electrolyte, effectively improved the battery's cycle stability and rate performance, and improved the battery's charge and discharge efficiency. DETAILED DESCRIPTION
[0032] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0033] The invention provides an electrolyte for a sodium ion battery and a sodium ion secondary battery using the electrolyte.
[0034] The electrolyte includes solvents, conductive salts, and additives.
[0035] Solvents
[0036] In the present invention, specifically, the solvent is a mixture of PC (propylene carbonate), FEC (fluoroethylene carbonate), and FEMC (methyl trifluoroethyl carbonate). In the present invention, the solvent composition ratio is PC:FEC:FEMC=4-5:2-3:2-3 (volume ratio). In the present invention, PC can be selected from 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0; FEC can be selected from 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0; FEMC can be selected from 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0. The above volume ratio values are all possible values.
[0037] The prior art recognizes that PC (propylene carbonate) has the characteristics of high dielectric constant and low viscosity. The high dielectric constant is conducive to the dissolution of sodium salts, ensuring that the electrolyte has good ionic conductivity. The low viscosity is conducive to the rapid migration of ions and improves the rate performance of the battery.
[0038] The fluorine atoms in FEC (fluoroethylene carbonate) have an electron-withdrawing effect, which makes FEC have excellent oxidation resistance and film-forming properties. During the battery charging and discharging process, FEC can preferentially decompose on the electrode surface to form a high-quality solid electrolyte interface (SEI) to protect the electrode material from the erosion of the electrolyte. In addition, the addition of FEC can also broaden the electrochemical window of the electrolyte and improve the high-voltage stability of the battery.
[0039] FEMC (methyl trifluoroethyl carbonate) can reduce the number of free solvent molecules in the electrolyte, thereby reducing the solubility of SEI components. The synergistic effect of FEMC and FEC can further optimize the solvation structure of the electrolyte and improve the stability of the electrolyte.
[0040] In the present invention, PC, as a representative of carbonate solvents, has the characteristics of high dielectric constant and low viscosity, which is conducive to the dissolution of sodium salts and the rapid migration of ions. Selecting PC as the basic component of the electrolyte can ensure that the electrolyte has good ionic conductivity. FEC has excellent antioxidant and film-forming properties due to the electron-withdrawing effect of its fluorine atoms. FEC can improve the oxidative stability of the electrolyte and form a high-quality SEI film on the electrode surface to protect the electrode material from corrosion. FEMC, as a low-polarity solvent, can reduce the number of free solvent molecules in the electrolyte and reduce the solubility of SEI components. At the same time, the synergistic effect of FEMC and FEC can further optimize the solvation structure of the electrolyte. Thereby ensuring the stability of the electrolyte while improving its cycle performance under high-voltage conditions.
[0041] Conductive salt
[0042] The present invention selects a mixed conductive salt of sodium perchlorate (NaClO4) and sodium hexafluorophosphate (NaPF6).
[0043] Sodium perchlorate is a commonly used conductive salt for sodium ion batteries, which has high ionic conductivity and good thermal stability. It can maintain high conductivity over a wide temperature range. Sodium hexafluorophosphate is another commonly used conductive salt for sodium ion batteries, which has good solubility and conductivity.
[0044] The ratio of sodium perchlorate to sodium hexafluorophosphate is in the range of (molar ratio) NaClO4:NaPF6=1:0.1 to 1:0.5.
[0045] The mass percentage of the conductive salt in the electrolyte is 10% to 25%.
[0046] additive
[0047] In sodium ion batteries, the selection of electrolyte additives is crucial to improving battery cycle stability and performance. The present invention uses sodium nitrate (NaNO3) and sodium acesulfame as electrolyte additives to optimize the composition of the electrolyte in a solvent environment based on propylene carbonate (PC).
[0048] As an effective electrolyte additive, sodium nitrate can be preferentially reduced on the negative electrode surface in sodium ion batteries to form a stable SEI. This SEI layer can inhibit the growth of sodium dendrites and improve the cycle stability of the battery. The amount of sodium nitrate added is 0.1%-2% of the total mass of the electrolyte. Within the appropriate addition range, sodium nitrate can significantly improve the performance of the battery.
[0049] Since nitrate ions (NO3 -) has a lower unoccupied electron energy level (LUMO), so it will be preferentially reduced on the negative electrode surface during the battery charge and discharge process. This preferential reduction characteristic helps to form a uniform SEI layer on the negative electrode surface. The reduction products of nitrate ions can participate in the formation of SEI, increasing the mechanical strength and chemical stability of the SEI layer. A stable SEI layer can effectively inhibit the growth of sodium dendrites and the decomposition of the electrolyte, thereby improving the cycle life and safety of the battery. The addition of sodium nitrate can also regulate the interfacial reaction between the electrolyte and the negative electrode and reduce the occurrence of side reactions. This helps to reduce the internal resistance of the battery and improve the coulombic efficiency and energy conversion efficiency of the battery.
[0050] As a new type of electrolyte additive, sodium acesulfame improves the interfacial properties of the electrolyte by participating in the formation of SEI, thereby improving battery performance. The addition amount of sodium acesulfame is also 0.1%-2% of the total mass of the electrolyte. Within the appropriate addition range, sodium acesulfame can significantly enhance the stability of SEI and the performance of the battery.
[0051] The decomposition products of sodium acesulfame can participate in the formation of SEI and increase the ratio of organic and inorganic components in the SEI layer. This optimized SEI layer has better mechanical properties and chemical stability, and can more effectively inhibit the growth of sodium dendrites and the decomposition of the electrolyte. The addition of sodium acesulfame can improve the wettability between the electrolyte and the electrode material, so that the electrolyte can cover the electrode surface more evenly. This helps to form a more uniform SEI layer and improve the performance consistency of the battery. Sodium acesulfame can also inhibit side reactions between the electrolyte and the electrode material, reduce the generation of harmful gases and the consumption of the electrolyte. This helps to reduce the internal resistance and self-discharge rate of the battery and improve the cycle stability and safety of the battery.
[0052] To make this organic electrolyte, follow the steps below:
[0053] The selected PC, FEC and FEMC are all high-purity reagents, and the moisture and impurity contents are lower than the specified standards. At the same time, the required sodium salt and other additives are prepared.
[0054] Moisture has a serious impact on the performance of the electrolyte, so all solvents need to be dried before preparation. Molecular sieves or vacuum drying ovens can be used for drying to ensure that the moisture content in the solvent is less than 10ppm.
[0055] In a protective gas atmosphere, the three solvents are mixed evenly in a predetermined ratio. Then, the conductive sodium salt and additives are added and stirred until they are completely dissolved. The stirring time is based on the standard to ensure that all ingredients are fully mixed.
[0056] The prepared electrolyte needs to be filtered through a membrane to remove possible solid particles and impurities. After filtering, the electrolyte should be stored in a dry, light-proof, sealed container to avoid contact with air and moisture.
[0057] The electrolyte is prepared by using the above ratio and method.
[0058] In the present invention, sodium nitrate is an effective electrolyte additive, which can be preferentially reduced on the negative electrode surface in a sodium ion battery to form a stable solid electrolyte interface (SEI), thereby inhibiting the growth of sodium dendrites and improving the cycle stability of the battery. In the present invention, the amount of sodium nitrate added is 0.1%-2% of the total mass of the electrolyte. For example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0.
[0059] As a new electrolyte additive, sodium acesulfame improves the interfacial properties of the electrolyte by participating in the formation of SEI, thereby improving battery performance. In the present invention, the addition amount of sodium acesulfame is 0.1%-2% of the total mass of the electrolyte. For example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0.
[0060] The present invention uses the above electrolyte to prepare a sodium ion secondary battery. The positive electrode and negative electrode of the sodium ion secondary battery are as follows:
[0061] positive electrode
[0062] The positive electrode active material is sodium vanadium phosphate (Na3V2(PO4)3, NVP), which is a high-performance positive electrode material for sodium ion batteries with high energy density, good thermal stability and long cycle life. Its structure makes the ion conductivity high and suitable for high-rate charge and discharge.
[0063] The amount of positive electrode active material (NVP) generally accounts for 70%-80% of the total mass of the positive electrode, and the rest is conductive agent (such as acetylene black) and binder (such as PVDF).
[0064] Manufacturing method:
[0065] Sodium vanadium phosphate, conductive agent and binder are mixed evenly in a certain ratio (7:2:1), and then an appropriate amount of solvent (such as N-methylpyrrolidone, NMP) is added to form a slurry. Use a coating machine to evenly coat the slurry on aluminum foil to form a positive electrode sheet. Place the coated positive electrode sheet in a vacuum oven and dry it at about 80°C for 12 hours to remove the solvent. After drying, cut the positive electrode sheet into the required size.
[0066] negative electrode
[0067] The negative electrode material is hard carbon, which is an amorphous carbon material with high specific surface area, good sodium insertion ability and low cost. It is one of the commonly used negative electrode materials in sodium ion batteries. The structural characteristics of hard carbon enable it to accommodate a large number of sodium ions, thereby providing a higher specific capacity.
[0068] The hard carbon material, conductive agent and binder are mixed evenly and coated on copper foil to form a negative electrode sheet, which is then dried and cut.
[0069] Subsequently, the sodium ion secondary battery was manufactured.
[0070] The diaphragm material is a polyolefin composite diaphragm.
[0071] The aluminum-plastic film specially used for soft-pack batteries is selected as the battery shell to ensure good air tightness and flexibility. According to the battery design, the positive electrode sheet, negative electrode sheet and separator are wound to form a battery core.
[0072] Place the battery core into the aluminum plastic film, making sure the positive and negative electrodes and the separator are positioned correctly.
[0073] The electrolyte is evenly injected into the battery core through precision injection equipment. Then, the aluminum-plastic film is heat-sealed to ensure the sealing of the battery.
[0074] Example: Preparation of electrolyte
[0075] PC, FEC and FEMC are dried separately through molecular sieve or vacuum drying oven to ensure that the moisture content is less than 10ppm.
[0076] In a protective gas (such as argon) atmosphere, PC, FEC and FEMC are evenly mixed in a volume ratio of 4.5:2.5:2.5.
[0077] Weigh appropriate amounts of sodium perchlorate and sodium hexafluorophosphate in a molar ratio of 1:0.3 and add them to the mixed solvent. The mass percentage of the conductive salt in the electrolyte is controlled to be 18%. Use a magnetic stirrer or a mechanical stirrer to stir until it is completely dissolved.
[0078] Sodium nitrate and sodium acesulfame were added to the electrolyte in amounts of 1% and 1.5% of the total mass of the electrolyte, respectively, and the mixture was stirred until the additives were completely dissolved.
[0079] Filter the prepared electrolyte through a filter membrane to remove possible solid particles and impurities. After filtering, store the electrolyte in a dry, light-proof, sealed container to avoid contact with air and moisture.
[0080] A high-performance sodium ion battery electrolyte is obtained by the above method, which has good ionic conductivity, oxidation stability and cycle performance.
[0081] Example: Manufacturing a sodium ion secondary battery
[0082] Sodium vanadium phosphate, acetylene black and PVDF are mixed evenly in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone (NMP) is added to form a slurry. The slurry is evenly coated on an aluminum foil using a coating machine to form a positive electrode sheet. The positive electrode sheet is placed in a vacuum oven and dried at 80°C for 12 hours to remove the solvent. After drying, the positive electrode sheet is cut into the required size.
[0083] The hard carbon material, acetylene black and PVDF are mixed evenly, coated on copper foil to form a negative electrode sheet, and then dried and cut into the required size.
[0084] A polyolefin composite diaphragm is selected as the diaphragm material.
[0085] Use the aluminum-plastic film specially used for soft-pack batteries as the battery shell. According to the battery design, wind the positive electrode sheet, negative electrode sheet and separator to form a battery core. Put the battery core into the aluminum-plastic film to ensure that the positive and negative electrodes and separator are positioned correctly.
[0086] The electrolyte prepared in the electrolyte embodiment is uniformly injected into the battery core through a precision liquid injection device; the aluminum-plastic film is heat-sealed to ensure the sealing of the battery.
[0087] A high-performance sodium ion secondary battery is obtained through the above method.
[0088] Adjust the components in the above two embodiments to obtain the following embodiments:
[0089]
[0090]
[0091] The present invention conducts multiple tests on sodium ion batteries, including electrical performance tests, safety tests, environmental adaptability tests, and reliability tests.
[0092] Electrical performance test
[0093] Electrical performance testing is the basis for evaluating the performance of sodium-ion batteries, and mainly includes tests on battery charging and discharging performance, cycle life, rate performance, and energy density.
[0094] The performance of the battery under different charging and discharging conditions is evaluated through constant current charge and discharge tests, AC impedance tests, etc. These tests can reveal important information such as the battery's charge and discharge efficiency and capacity attenuation.
[0095] Under specified environmental conditions, the battery life is measured by cyclic charging and discharging in a specific cyclic charging and discharging method. Cycle life is an important indicator to measure the long-term performance of batteries and is of great significance for evaluating the service life and replacement cycle of batteries.
[0096] Rate performance test. By testing the performance of the battery at different charge and discharge rates, the battery's response ability and stability under high-rate charge and discharge conditions are evaluated. Rate performance is crucial for the application of batteries in fast charge and discharge situations.
[0097] Energy density test. Measure the energy output per unit volume or unit mass of the battery to evaluate the energy density of the battery. Energy density is an important indicator to measure the energy storage capacity of the battery, which is of great significance for improving the energy efficiency of the battery and reducing the size of the battery.
[0098] Safety Testing
[0099] Safety testing is used to test the safety of sodium-ion batteries in practical applications, mainly including safety testing under abnormal conditions such as overcharging and over-discharging.
[0100] Overcharge test: By overcharging the battery, the performance and safety of the battery in an overcharged state are evaluated. Overcharging may cause problems such as excessive internal pressure and temperature rise in the battery, and in severe cases may cause fire or explosion.
[0101] Over-discharge test. By over-discharging the battery, the performance and safety of the battery under over-discharge condition are evaluated. Over-discharge may cause loss of active materials inside the battery, capacity attenuation and other problems.
[0102] Short circuit test. By simulating the short circuit inside the battery, the battery's ability to withstand a short circuit and its response to a short circuit can be evaluated. A short circuit may cause a sharp increase in the battery's internal current and a rapid rise in temperature.
[0103] High temperature testing. Measure the temperature changes of sodium-ion batteries to evaluate the performance and stability of the battery at high temperatures. High temperatures may cause problems such as accelerated chemical reactions inside the battery and thermal runaway.
[0104] The above Examples 1-20 were subjected to charge and discharge tests.
[0105] The test method is as follows:
[0106] Use a Landian multi-channel battery test system (such as LAND CT2001A) to perform charge and discharge tests.
[0107] Test conditions: constant current charge and discharge, voltage range set to 4.5V.
[0108] Test times: 10, 100, 500 and 1000 charge and discharge cycles respectively.
[0109] The discharge capacity after each cycle was recorded.
[0110]
[0111]
[0112] The rate performance test of Examples 1-20 was continued. The following table lists the discharge capacity retention rates of Examples 1-20 at different charge and discharge rates (0.5C, 1C, 2C, 5C) to evaluate the rate performance of the battery. The discharge capacity retention rate refers to the ratio of the discharge capacity at a specific rate to the discharge capacity at a 0.5C rate, which is used to reflect the performance retention of the battery under high rate charge and discharge conditions.
[0113]
[0114]
[0115] In the above table: the discharge capacity at a discharge rate of 0.5C is assumed to be the basic discharge capacity of each embodiment, which is used for comparison of subsequent rate performance.
[0116] Discharge capacity retention rate: It indicates the retention of discharge capacity at different rates relative to the discharge capacity at 0.5C rate. It is an important indicator for evaluating battery rate performance.
[0117] Rate selection: Four rates, 0.5C, 1C, 2C and 5C, were selected for testing to cover the range of charge and discharge rates from low to high.
[0118] In the invention, the electrolyte is composed of three solvents: PC (propylene carbonate), FEC (fluoroethylene carbonate) and FEMC (methyl trifluoroethyl carbonate). The selection of these three solvents is not random, but based on their unique properties. PC has the characteristics of high dielectric constant and low viscosity, which is conducive to the dissolution of sodium salts and the rapid migration of ions; FEC has excellent antioxidant and film-forming properties due to the electron-withdrawing effect of its fluorine atoms, which can improve the oxidation stability of the electrolyte and form a high-quality SEI film on the electrode surface to protect the electrode material from corrosion; FEMC, as a low-polarity solvent, can reduce the number of free solvent molecules in the electrolyte, reduce the solubility of SEI components, and synergize with FEC to further optimize the solvation structure of the electrolyte. The mixing of these solvents in different proportions can balance the various properties of the electrolyte, thereby meeting the needs of the battery at high-rate charge and discharge.
[0119] As an effective electrolyte additive, sodium nitrate can be preferentially reduced on the surface of the sodium metal negative electrode to form a stable solid electrolyte interface (SEI), thereby inhibiting the growth of sodium dendrites and improving the cycle stability of the battery. During high-rate charge and discharge, the rapid migration and insertion / deinsertion process of sodium ions may lead to instability on the negative electrode surface, while the SEI film formed by sodium nitrate can effectively protect the negative electrode material and reduce the occurrence of side reactions, thereby improving the rate performance of the battery. As a new type of electrolyte additive, sodium acesulfame improves the interfacial properties of the electrolyte by participating in the formation of SEI, thereby improving battery performance. During high-rate charge and discharge, the interfacial reaction between the electrolyte and the electrode material will be more intense, and sodium acesulfame can optimize this interfacial reaction, improve the migration rate of ions and the charge and discharge efficiency of the battery.
[0120] Subsequently, safety tests were conducted on Examples 1-20.
[0121] Safety test results of Examples 1-20
[0122] 1. Overcharge test
[0123] The overcharge test is designed to evaluate the performance and safety of a battery when it exceeds its rated charge capacity. In the test, the battery is charged to 150% of its rated capacity and its voltage, temperature, shape change, and whether there is leakage, smoking or explosion are observed.
[0124]
[0125]
[0126] 2. Over discharge test
[0127] The over-discharge test evaluates the performance and safety of the battery when it is below its rated discharge capacity. In the test, the battery is discharged to 0% of its rated capacity and its voltage, temperature, shape changes, and whether there is leakage, damage, etc. are observed.
[0128]
[0129]
[0130] 3. Short circuit test
[0131] The short-circuit test simulates the short circuit inside the battery and evaluates the battery's response and safety during a short circuit. During the test, the battery is forced to short-circuit and its current, voltage, temperature changes, and whether there is smoke, explosion, etc. are observed.
[0132]
[0133]
[0134] 4. High temperature test
[0135] High temperature testing evaluates the performance and stability of batteries in high temperature environments. During the test, the battery is placed in a high temperature environment (such as 60°C) and its voltage, current, temperature changes, and whether there is leakage or damage are observed.
[0136]
[0137]
[0138] From the above tests, it can be seen that the sodium ion batteries in Examples 1-20 all showed good safety in overcharge, overdischarge, short circuit and high temperature tests.
[0139] In the present invention, there is a synergistic effect between the solvent and the additive. First, the addition of additives enriches the components of SEI and improves the stability and mechanical strength of SEI. The addition of sodium nitrate and sodium acesulfame can increase the ratio of organic components and inorganic components in the SEI layer, forming a more stable SEI layer. In addition, the combined action of the solvent and the additive can regulate the interfacial reaction between the electrolyte and the electrode material and reduce the occurrence of side reactions. The synergistic effect of FEC and sodium nitrate can inhibit the side reactions between the electrolyte and the negative electrode, reducing the internal resistance and self-discharge rate of the battery. The addition of additives can also broaden the electrochemical window of the electrolyte and improve the high-voltage stability of the battery. For example, the addition of FEC can significantly improve the antioxidant properties of the electrolyte, allowing the battery to work stably at a higher voltage.
[0140] In the present invention, the presence of conductive salt provides sufficient ion sources, and the addition of additives further optimizes the migration path and rate of ions. This synergistic effect significantly improves the ionic conductivity of the electrolyte, thereby improving the performance of the battery. The combined effect of conductive salts and additives enhances the stability of SEI. For example, the synergistic effect of NaPF6 and sodium nitrate can form a more stable and uniform SEI layer, inhibiting the growth of sodium dendrites and the decomposition of the electrolyte. The synergistic effect of sodium perchlorate and sodium acesulfame reduces the consumption of electrolyte and the generation of harmful gases, thereby reducing the internal resistance and self-discharge rate of the battery, and improving the cycle stability and safety of the battery.
[0141] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An electrolyte for a sodium ion battery, characterized in that: include: A solvent, wherein the solvent is a mixture of propylene carbonate (PC), fluoroethylene carbonate (FEC) and methyl trifluoroethyl carbonate (FEMC); Conductive salt, wherein the conductive salt is a mixture of sodium perchlorate (NaClO4) and sodium hexafluorophosphate (NaPF6); Additives, the additives comprising sodium nitrate (NaNO3) and acesulfame sodium.
2. The electrolyte according to claim 1, characterized in that The volume ratio of each component in the solvent is PC:FEC:FEMC is 4-5:2-3:2-3.
3. The electrolyte according to claim 1, characterized in that The molar ratio of the sodium perchlorate to sodium hexafluorophosphate is 1:0.1 to 1:0.5, and the mass percentage of the conductive salt in the electrolyte is 10% to 25%.
4. The electrolyte according to claim 3, characterized in that The mass percentage of the conductive salt in the electrolyte is 18%.
5. The electrolyte according to claim 1, characterized in that The addition amount of the sodium nitrate and sodium acesulfame is 0.1%-2% of the total mass of the electrolyte respectively.
6. The electrolyte according to claim 1, characterized in that The following steps are used to make it: Dry PC, FEC and FEMC to ensure the moisture content is less than 10ppm; In a protective gas atmosphere, the three solvents are mixed evenly according to a predetermined ratio; Add conductive sodium salt and additives and continue stirring until completely dissolved; Filter the prepared electrolyte through a filter membrane to remove possible solid particles and impurities.
7. A sodium ion secondary battery, characterized in that: Use the electrolyte according to any one of claims 1 to 6.
8. The sodium ion secondary battery according to claim 7, characterized in that: The positive electrode active material of the sodium ion secondary battery is sodium vanadium phosphate (Na3V2(PO4)3, NVP), and the amount of the positive electrode active material accounts for 70%-80% of the total mass of the positive electrode.
9. The sodium ion secondary battery according to claim 7, characterized in that: The negative electrode material of the sodium ion secondary battery is hard carbon.
10. The sodium ion secondary battery according to claim 7, characterized in that: The manufacturing steps of the sodium ion secondary battery include: The positive electrode active material, the conductive agent and the binder are mixed evenly and coated on the aluminum foil to form a positive electrode sheet; The negative electrode material, the conductive agent and the binder are mixed evenly and coated on the copper foil to form a negative electrode sheet; Winding the positive electrode sheet, the negative electrode sheet and the separator to form a battery core; The battery cell is placed in a battery case, the electrolyte is injected, and the battery case is sealed.